Acknowledgement to reviewers 12(3) - Kumar, Satish (Journal of Cereal Research, 2020)
The editorial team greatly acknowledge the assistance of reviewers who have dedicated their precious time and expertiseto the journal’s grueling editorial process over the past four months, regardless of whether the articles are finally publishedor not. In this issue a total of 15 articles were published. The editors would like to express their sincere gratitude to thefollowing reviewers for their unstinting contribution for this issue of Journal of Cereal Research, Volume 12, issue 3 in 2020